2013
DOI: 10.1177/107327481302000208
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age on Morbidity and Mortality following Esophagectomy for Esophageal Cancer

Abstract: Background: In patients with esophageal cancer, treatment decisions often involve a balance between a high-risk procedure and the chance for long-term benefi t. The decision

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
1
24
0
1
Order By: Relevance
“…Age has been demonstrated in several studies to correlate with higher rates of morbidity and mortality as well as worse survival (16)(17)(18)(19)(20) (16). Several other studies, however, have found that when adjusted for comorbid conditions, age itself is not a predictor of post-operative morbidity (2,(21)(22)(23)(24)(25)(26). In a review of 685 patients undergoing esophagectomy between 1994 and 2012 at a single institution cancer center, McLoughlin et al found that the only significant predictor of overall survival and disease free survival on multivariate analysis was neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Age has been demonstrated in several studies to correlate with higher rates of morbidity and mortality as well as worse survival (16)(17)(18)(19)(20) (16). Several other studies, however, have found that when adjusted for comorbid conditions, age itself is not a predictor of post-operative morbidity (2,(21)(22)(23)(24)(25)(26). In a review of 685 patients undergoing esophagectomy between 1994 and 2012 at a single institution cancer center, McLoughlin et al found that the only significant predictor of overall survival and disease free survival on multivariate analysis was neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 85%
“…Surgical resection is an integral part of the treatment algorithm for early stage and locally advanced esophageal cancer. Unfortunately, the morbidity associated with esophagectomy can be high and is estimated in the literature to be between 25% and 50% (2,13,14). Pulmonary and cardiovascular complications such as atelectasis, pneumonia, and atrial fibrillation, in addition to wound infection, anastomotic leak, and chylothorax are among the most commonly seen post-operative complications and may increase the risk of mortality (13,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall morbidity for esophagectomy is estimated to range between 25% and 50% 28 . Although some surgical series suggest that medical comorbidities, rather than actual age, are the most important factors in predicting perioperative morbidity and mortality 26,27,29 , advanced age appears to be an independent risk factor for perioperative mortality in other reports 8,30 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, age was not found to be significantly associated with os on either univariate or multivariate analysis. Some studies have also suggested that, after careful adjustment for comorbidities, age itself has no effect on survival in patients with esophageal cancer 26,27 .…”
Section: Discussionmentioning
confidence: 99%